Effects of the COVID-19 Pandemic on Participation in Physical Activity of Individuals with Autism Spectrum Disorder: The True-Life Experiences of Parents - Kübra Durmuş; Halil Sarol; Rıfat Kerem Gürkan (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Özel Eğitim Dergisi)
Introduction: The COVID-19 pandemic rapidly spread throughout the whole world and negatively affected individuals’ participation in physical activity. In this context, the purpose of the research is to investigate the effects of the COVID-19 pandemic on the participation in physical activity of individuals with Autism Spectrum Disorder (ASD) from the perspective of their parents.Method: Ten parents (6 mothers and 4 fathers) with children diagnosed with ASD constituted the sample group for the research designed by the phenomenological qualitative research method. A semi-structured interview form and a personal information form were used as data collection tools. The data analysis was performed using the content analysis method.Findings: In the direction of the findings obtained from the research, four inclusive themes were determined. These are a) the effects of the pandemic on life; b) the difficulties encountered during the period of the pandemic; c) the necessity of physical activity; and d) the changing events. Under these themes, there are 12 sub-themes in total.Discussion: The parents expressed that the practices performed for the sake of decreasing the propagation rate of the virus had negatively affected especially the education, parent relationships, and active lifestyles of children with ASD. According to the parents, the physical activity habits of children with ASD significantly changed, and usually, home-based events were performed during the restrictions. The parents specified that they had understood how extremely important the participation in physical activity of children with ASD was during the period of the pandemic.